Imitation of life [videorecording (DVD)] - Turner, Lana, 1921-1995; Gavin, John, 1931-2018; Dee, Sandra; Alda, Robert; O'Herlihy, Dan, 1919-2005; Donahue, Troy, 1936-2001; Hurst, Fannie, 1889-1968 (Universal Studios Home Video, 2002)
The story of two widows and their troubled daughters. In the search for success as an actress, Lora neglects her daughter. Lora's black housekeeper's daughter repudiates her mother by trying to pass for white. As the years pass, each of the four women realizes that she has been living an emotionally fruitless existence.